A Novel Strategy in Electromagnetic Wave Absorbing and Shielding Materials Design: Multi‐Responsive Field Effect. Issue 2 (27th November 2021) - Zhao, Yue; Hao, Lele; Zhang, Xindan; Tan, Shujuan; Li, Haohang; Zheng, Jing; Ji, Guangbin
Abstract : The electromagnetic (EM) devices have been widely used in communication, electrical engineering, and medical care. However, EM device is a double‐edged sword for its convenience is followed by signal pollution and radiation. Electromagnetic interference (EMI) combat has brought lots of attention to researchers in this field. Researchers have made great efforts in developing electromagnetic wave absorbing and shielding (EMAS) materials to reduce EM wave power density to solve the above problem. However, the great majority of reported EMAS materials are powders and coatings, which possess merely EMAS property. Modern practical application has abundant multiple scenes, including high temperature, intense light, water flow, etc. Under the circumstances, EMAS materials should be functionalized with outstanding tunable absorption bands. Based on field theory in physics, multiexternal fields‐responsive materials are an effective method to deal with the above urgently unsolved problem. Thus, herein, different external field‐responsive materials, including temperature, light, space–time, electrical, wind, density, and flow fields, are focused on. Various action mechanisms, materials synthesis methods, and different macrostructures are summarized in detail. Meanwhile, the developing trends of novel external field‐responsive materials are also discussed in order. Finally, the challenges of designing new type of EMAS devices are mentioned. Abstract : The current multifunctional electromagnetic wave absorbing and shielding (EMAS) materials are reviewed. An external field‐responsive strategy is proposed to enrich application scenes, including temperature field, light field, space–time field, electrical field, wind field, density field, and flow field. Action mechanisms and EMAS performance improvements are discussed and concluded.